PENGUATAN NILAI KARAKTER NASIONALISME MELALUI MAKNA LAGU NASIONAL UNTUK SISWA SDN GADANG 3 MALANG - Rahman, M. Alfan Fadlur; Gutama, Andika; Rahayunita, Cicilia Ika (Sindoro: Cendikia Pendidikan, 2024)
Currently, the practice of singing the national anthem has been widely implemented in schools. But teachers need specific sessions to provide an overview of the meaning of the national anthem being sung. The low understanding of national songs and students' tendency towards pop songs indicate a challenge in the implementation of nationalist character. The purpose of the research is to describe the strengthening of nationalist character values and the role of teachers in the process of strengthening nationalist character values. Qualitative methods are methods used in research involving fifth-grade students, fifth-grade teachers, and the school principal as data sources. Data collection was conducted through questions about how the strengthening of nationalism character values through the meaning of national songs shows that the strengthening of nationalism character is carried out regularly at school. The teacher guides students in singing and understanding the meaning of the national anthem, and relates it to daily life. With the program to strengthen the values of nationalism through the meaning of the national anthem, it will effectively shape the national character values of the students and ensure they do not forget the national anthem, which is a symbol of the Indonesian nation and state. Pada saat ini pembiasaan bernyanyi lagu nasional sudah banyak yang menerapkan disekolah. Tetapi para guru perlu sesi tertentu untuk memberikan Gambaran makna lagu nasional yang dinyanyikan. Rendahnya pemahaman terhadap lagu nasional dan kecenderungan siswa terhadap lagu pop menunjukkan tantangan dalam penerapan karakter nasionalisme. Tujuan penelitian adalah mendeskripsikan penguatan nilai karakter nasionalisme dan peran guru dalam proses penguatan nilai karakter nasionalisme. Metode kualitatif adalah metode yang digunakan dalam penelitian dengan melibatkan siswa kelas V, guru kelas V, dan kepala sekolah sebagai sumber data. Pengumpulan data dilakukan melalui pertanyaan tentang bagaimana penguatan nilai karakter nasionalisme melalui makna lagu nasional, menunjukkan penguatan karakter nasionalisme dilakukan secara rutin disekolah. Guru membimbing siswa dalam menyanyikan dan memahami makna lagu nasional, serta mengaitkannya dengan kehidupan sehari-hari. Dengan program penguatan nilai karakter nasionalisme melalui makna lagu nasional akan membentuk nilai karakter nasional siswa dengan baik dan tidak melupakan lagu nasional yang merupakan simbol bangsa dan negara Indonesia.